Fatigue behavior of Y-TZP ceramic after surface treatments - Amaral, Marina [UNESP] (2016)
Objectives: The aim of this study was to evaluate the effect of three surface treatments on the biaxial flexural strength before and after mechanical cycling, and fatigue limit of a Y-TZP ceramic. Methods: Disc-shaped specimens were produced and three surface conditions were tested: CT (as-sintered, untreated), GL (thin layer of porcelain glaze), and AA (air abrasion with 30 mu m silica particles). Profilometric and phase transformation analyses were performed. Disks were submitted to biaxial flexural strength (BFS) before and after mechanical cycling (100 N, 2 x 10(6) cycles) and staircase approach (n=20). The flexural fatigue limits (FFLs) were obtained at 10(2), 10(3), 10(4) and 10(5) cycles. Results: Tetragonal to monoclinic transformation was only observed for AA group (9.46% of monoclinic phase). Glazed group presented the highest Ra values. Flexural strength was higher for AA group; CT and GL groups were similar. The reliability was similar between groups. The mechanical cycling at 100 N did not affected flexural strength. FFLs were higher for AA group, and the three surface treatments presented decrease in strength according to the increase in number o cycles. (C) 2015 Elsevier Ltd. All rights reserved.